Penatalaksanaan Fisioterapi Pediatric Pada Kasus Bronkopneumonia - Dewi Aprillya Sekararum; Syavina Nurameylia; Fatimatuzahroh Fatimatuzahroh; Dini Nur Alpiah (JURNAL ILMIAH RESEARCH STUDENT, 2025)
Bronchopneumonia is one of the leading causes of morbidity and mortality in children, particularly in developing countries. This disease is characterized by inflammation of the bronchioles and alveoli due to infection by bacteria, viruses, or other microorganisms. Clinical symptoms include fever, productive cough, shortness of breath, and the presence of crackles upon auscultation. Physiotherapy management for children with bronchopneumonia may include inhalation therapy using a nebulizer and chest clapping techniques to help clear the airways, improve lung ventilation, and reduce the level of dyspnea. This study utilized a case study method involving three pediatric patients diagnosed with bronchopneumonia. Physiotherapy interventions included nebulizer administration (0.25 ml salbutamol diluted in 0.9% NaCl to a total volume of 2 ml, administered twice daily for three days) and chest clapping (10–15 minutes, 2–3 times daily). Evaluation was conducted using the Borg scale for dyspnea and assessments of sleep quality. The results showed a decrease in Borg scale scores and an improvement in sleep quality in all patients following the intervention. This physiotherapy intervention was clinically proven to be effective in supporting the recovery of children with bronchopneumonia. In conclusion, the combination of inhalation therapy and chest clapping is a supportive physiotherapy approach that is safe, non-invasive, and effective in improving respiratory conditions in pediatric patients